FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN INDUSTRI KREATIF DI INDONESIA (TAHUN 2002 – 2008) - Afif Leksono; Purbayu Budi Santosa (Diponegoro Journal of Economics, 2014)
ABSTRACTCreative industries are those industries who have potency to contribute in economic growth, reflected in the increase of Gross Domestic Product (GDP) in Creative Industry component. Therefore, the analysis of factors affect GDP in creative industries component is needed in order to contribute optimally in the increase of it.The purpose of the research is analyzing labor, export value, import value, and company number as the factors affect GDP in creative industries component in Indonesia 2002-2008. This research uses secondary data with panel dataanalysis tool that consists of time series data 2002-2008 and cross section data of 10 subsectors of creative industries in Indonesia. The mothod uses is linear regression analysis panel data with Ordinary Least Square method (OLS).The result shows that labor and import value variabel have positive and significant impact on GDP in creative industries while export value and company number have negative and significant impact on GDP in creative industries.